Evaluation of Proposed Ouagadougou-Donsin Airport Development, Burkina Faso - World Bank (Washington, DC, 2013)
The Government of Burkina Faso (GoBF) has indicated that it wishes to relocate the current international airport of Ouagadougou, which lies close to the centre of the capital, to an alternative site at Donsin, 35 km northwest of the city. This report briefly describes the economy of Burkina Faso within which the airport operates, the current infrastructure of the existing airport and examines the reasons why the GoBF believes that it is inadequate to meet the projected future demand for aviation services. It also considers the proposed relocation of the existing airport within the context of the Government s overall policy for the strategic development of the country s transport infrastructure and tourism; the current institutional and regulatory structure of civil aviation in Burkina Faso and the division of responsibilities between key statutory and supra-national bodies; the urban development plan for the city of Ouagadougou and the area of Grand Ouaga; and the Government s broader policy objectives relating to economic reform, decentralization and social development.